EFEKTIVITAS PEMBELAJARAN DALAM JARINGAN DI TENGAH PANDEMI COVID-19 DI SD NEGERI KEMLOKO TEMANGGUNG - Hamidulloh Ibda; Nadia Rena Sari (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2020)
The impact of covid-19 requires several local governments to decide on implementing policies to dismiss students and implement online or online learning systems. This government policy has been effectively enforced in several provinces in Indonesia since March 2020. However, this does not apply to several schools in Temanggung Regency. The learning system in a network is a learning system without face to face directly between teachers and students but is carried out online using the internet network. This study aims to determine the effectiveness of online learning activities at SD Kemloko Temanggung during the Covid-19 pandemic. This study uses qualitative methods and uses interview and observation data collection techniques. The results showed a lack of effectiveness during home learning. Students cannot interact directly with teachers and friends, students do assignments and watch television accompanied by their parents and students have difficulty receiving understanding of the material.